GSK3β Plays a Negative Role During White Spot Syndrome Virus (WSSV) Infection by Regulating NF-κB Activity in Shrimp Litopenaeus vannamei - Zhang, Shuang; Zhu, Lulu; Hou, Cuihong; Yuan, Hang; Yang, Sheng; Dehwah, Mustafa Abdo Saif; Shi, Lili (Frontiers in Immunology, 2020)
Glycogen synthase kinase-3 (GSK3), a cytoplasmic serine/threonine-protein kinase involved in a large number of key cellular processes, is a lesser-known signalling molecule in the field of virus research. In this study, a GSK3 protein possessing a high similarity with GSK3β homologs from other species in Litopenaeus vannamei (designated as LvGSK3β) was obtained. LvGSK3β was expressed constitutively in healthy L. vannamei with the highest expression level in the intestine while the lowest was in the eyestalk. White spot syndrome virus (WSSV) reduced LvGSK3β expression was in immune tissues including the haemocyte, intestine, gill and hepatopancreas. The inhitition of LvGSK3β resulted in significantly higher survival rates of L. vannamei in response to WSSV infection than the control group, and significantly lower WSSV viral loads in LvGSK3β-inhibited L. vannamei were observed. Knockdown of LvGSK3β by RNAi resulted in increases in the expression of LvDorsal and several NF-κB driven antimicrobial peptide (AMP) genes (including ALF, PEN and crustin), but a decrease in LvCactus expression. Accordingly, over-expression of LvGSK3β could reduce the promoter activity of LvDorsal and several AMPs, while the promoter activity of LvCactus was increased. Electrophoretic mobility shift assays (EMSA) showed that LvDorsal could bind to the promoter of LvGSK3β. The interaction between LvGSK3β and LvDorsal or LvCactus was confimed using co-immunoprecipitation (Co-IP) assays. In addition, the expression of LvGSK3β was dramatically reduced by knockdown of LvDorsal. In summary, the results presented in this study suggest that LvGSK3β has a negative effect on L. vannamei by mediateing a feedback regulatory loop of the NF-κB pathway when it is infected by WSSV.